Goals and feasibility of the Deep Space Quantum Link - Mazzarella, Luca; Mohageg, Makan; Strekalov, Dmitry V.; Zhai, Aileen; Israelsson, Ulf; Matsko, Andrey; Yu, Nan; Anastopoulos, Charis; Carpenter, Bradley; Gallicchio, Jason; Hu, Bei Lok; Jennewein, Thomas; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2021)
In this article, we review the proposed experiments for the Deep Space Quantum Link (DSQL) mission concept aiming to probe gravitational effects on quantum optical systems. Quantum theory and general relativity are the two most successful frameworks we have to describe the universe. These theories have been validated through experimental confirmations in their domains of application— the macroscopic domain for relativity, and the microscopic domain for quantum theory. To date, laboratory experiments conducted in a regime where both theories manifest measurable effects on photons are limited. Satellite platforms enable the transmission of quantum states of light between different inertial frames and over distances impossible to emulate in the laboratory. The DSQL concept proposes simultaneous tests of quantum mechanics and general relativity enabled by quantum optical links to one or more spacecrafts.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Foundational quantum theory; General relativity; Quantum optics